IC 8959 Economic And Technical Evaluation Of The Sulfurous Acid-Caustic Purification Process For Producing Alumina From Kaolinitic Clay - Deborah A. Kramer (The National Institute for Occupational Safety and Health (NIOSH), 1983)
An economic and technical evaluation of a proposed process to recover alumina by leaching calcined kaolinitic clay with sulfurous acid is presented in this Bureau of Mines report. After the insoluble portion of the clay has been removed by leaching, monobasic aluminum sulfite is precipitated from the pregnant leach solution by partial hydrothermal decomposition. Further heating completes the decomposition to an impure alumina hydrate. This intermediate is purified in a modified Bayer process, which includes dissolving the alumina hydrate in a caustic solution at high temperature and pressure, then decreasing the temperature and pressure to precipitate alumina trihydrate. Calcining the trihydrate produces the alumina product. A cost estimate was prepared for a plant producing 1,000 tons of alumina per day, 350 d/yr. The estimated operating cost is approximately $475 per ton of alumina. This is substantially higher than a comparable estimated operating cost for the Bayer process of $250 per ton of alumina. The proposed process does not appear economically attractive, even as a method to modify a current Bayer processing plant to use a kaolinitic clay feed. High capital costs and high energy requirements make the process prohibitively expensive.